Peran Kelembagaan dalam Program Upaya Khusus (UPSUS) Tanaman Jagung Berbasis Kearifan Lokal di Kabupaten Timor Tengah Utara - Marsianus Marsi Falo; Sugiyanto Sugiyanto; Keppi Sukesih; Yayuk Yuliati (AGRIMOR, 2022)
The involvement of all community components is a very important indicator for the success of the agricultural sector development process. The whole community can participate in agricultural development if the agricultural development program can be communicated according to regional conditions.The method used in this study is the Mix Method, which is a collaboration between quantitative and qualitative methods using a sequential explanatory model design where the first order uses quantitative methods, and the second uses qualitative methods. The population in this study were corn farmers who were members of the Corn Plant Upsus program in Insana District, TTU Regency, amounting to 270 farmers. the method of determining the size of the sample is calculated using the Slovin formula as many as 161 respondents. The primary data collection method is through a questionnaire that has been prepared in August-December 2019. Secondary data collection is carried out by collecting data from the Agriculture Service, BPS and related agencies.The analytical technique used in this study uses descriptive analysis, Miles and Hubermann analysis and Nvivo 12 analysis. The results of the analysis show that the characteristics of farmers (age is in the adult category, formal education, non-formal education is in the low category, farmer experience is in the high category, while broad In general, farmers are aware that there are government policies, institutions that provide capital, and the role of farmer groups but have not been utilized due to limited information that is less accessible to farmers.